2022
DOI: 10.3389/fpls.2022.997292
|View full text |Cite
|
Sign up to set email alerts
|

Root exudates and rhizosphere soil bacterial relationships of Nitraria tangutorum are linked to k-strategists bacterial community under salt stress

Abstract: When plants are subjected to various biotic and abiotic stresses, the root system responds actively by secreting different types and amounts of bioactive compounds, while affects the structure of rhizosphere soil bacterial community. Therefore, understanding plant–soil-microbial interactions, especially the strength of microbial interactions, mediated by root exudates is essential. A short-term experiment was conducted under drought and salt stress to investigate the interaction between root exudates and Nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…However, Menendez-Serra et al (2022) found that the microbial co-occurrence network was stable in ephemeral saline lakes under severe salinity fluctuations. Additionally, another study reported that the connectivity and complexity of the rhizosphere bacterial co-occurrence network were lowered in response to salt stress in Nitraria tangutorum ( Pan et al, 2022 ). The conflicting results suggest that besides salt, plant root exudates should not be ignored in the construction of co-occurrence networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Menendez-Serra et al (2022) found that the microbial co-occurrence network was stable in ephemeral saline lakes under severe salinity fluctuations. Additionally, another study reported that the connectivity and complexity of the rhizosphere bacterial co-occurrence network were lowered in response to salt stress in Nitraria tangutorum ( Pan et al, 2022 ). The conflicting results suggest that besides salt, plant root exudates should not be ignored in the construction of co-occurrence networks.…”
Section: Discussionmentioning
confidence: 99%
“…The conflicting results suggest that besides salt, plant root exudates should not be ignored in the construction of co-occurrence networks. Pan et al (2022) reported that salt stress caused significant differences in the root exudates of N. tangutorum , especially organic acids, growth hormones, and sugars. In general, root exudate composition and quantity can change under abiotic stresses including drought ( Vives-Peris et al, 2018 ) and salinization ( Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the "circlize" package in R software (4.1) was used to analyze the level of bacteria and fungi community. Gammaproteobacteria and Bacteroidota were defined as r-strategist bacteria, whereas Alphaproteobacteria and Acidobacteriota were defined as K-strategist bacteria according to the main idea of this study and previous studies [20,40]. The physicochemical properties and enzymatic activities of the 27 soil samples were analyzed using Spearman's correlation, and the Mantel test was used to describe the correlation [41].…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the relationship between r/K-strategist bacteria and functional fungi more intuitively, we calculated the Spearman coefficients for the OTUs of r/K-strategist bacteria and fungi in the three sampling plots (|r| > 0.9, p < 0.001) and then established the co-occurrence network with established data (e.g., showing the number of nodes in Gammaproteobacteria, Bacteroidota, Alphaproteobacteria, Acidobacteriota, and fungi) [20]. We further identified environmental factors affecting soil microbial communities and composition through random forest analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation